2023
DOI: 10.3389/fspor.2023.1250223
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in male youth football: a one season prospective cohort study of 223 Danish elite players

Thomas Rostgaard Andersen,
Andreas Drevsfeldt,
Sören Möller
et al.

Abstract: ObjectivesThis study prospectively investigated injury prevalence, incidence, and burden in male elite under-17 football players (N = 223) during a full season.MethodsThe players weekly completed a standardized web-based injury survey (OSTRC-H2) and a physical exposure report throughout the study.ResultsAverage weekly response rate was 89.5%. Football exposure accounted for 52.4% of total physical exposure. On average (±SD), the players participated in individual football, strength, and rehabilitation practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
(82 reference statements)
1
2
0
Order By: Relevance
“…In the current study, muscle injuries constituted the most prevalent type, making up 61.5% of all reported injuries, with quadriceps and hamstring injuries being equally common and predominantly occurring during training sessions. The results of the current study are consistent with previous studies [11,12] that found that knee injuries caused the highest burden among injuries and that muscular injuries in general were the most common in youth football players. However, no direct comparison can be conducted because these studies do not specifically address the incidence of knee muscle injuries in this population.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, muscle injuries constituted the most prevalent type, making up 61.5% of all reported injuries, with quadriceps and hamstring injuries being equally common and predominantly occurring during training sessions. The results of the current study are consistent with previous studies [11,12] that found that knee injuries caused the highest burden among injuries and that muscular injuries in general were the most common in youth football players. However, no direct comparison can be conducted because these studies do not specifically address the incidence of knee muscle injuries in this population.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, continuous involvement in football activities promotes the development of muscle imbalances [27], amplifying susceptibility to knee injuries [20]. This assumption is supported by Andersen et al [12] who identified a higher injury incidence rate per 1000 h during match play compared to team practice, suggesting that the intensity and duration of football exposure may impact the risk of knee injuries. Another study reported an overall injury incidence of 12.0 per 1000 h, with a heightened burden observed in the U16 age group [22].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation